Pelaksanaan Disiplin Aparatur Sipil Negara di Lingkungan Pemerintah Kabupaten Klungkung - Ni Putu Ayu Sutarini Dewi; I Gusti Bagus Suryawan; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
In order to realize national goals, ASN is in charge of providing public services. In serving the community, there are still many ASNs whose performance is not satisfactory in serving the community and many ASNs that violate disciplinary regulations. Discipline violations of the State Civil Apparatus include disobeying obligations and or violating the prohibition of the provisions of the ASN discipline, both those carried out inside and outside working hours. The problem of this research is about the application of penalties to the State Civil Apparatus who violate discipline and inhibiting factors in imposing sanctions. The method used in this study is empirical research with primary and secondary legal materials and legal material collection techniques by directly dropping space, interviews and literature studies. The results of the study were the application of penalties against ASN that violated the rules according to the level of violations committed and applied in accordance with Law No. 53 of 2010. The factors that become a barrier in the implementation of sanctions in the Klungkung Regency Government Environment are caused by the lack of strict attitude of the superiors and the high level of nepotism or kinship system as well as the political conditions in the Klungkung Regency government in general and the Secretariat in particular .